Clinical and radiographic evaluation of pure beta-tricalcium phosphate and autogenous bone graft in treatment of two to three-wall periodontal defects - Soleymani Shayeste Y; Khorsand A; Mahvidy Zade S; Nasiri M (Tehran University of Medical Sciences, 2010)
"nBackground and Aims: Intrabony periodontal defects are one of the important problems in periodontal diseases. Treatment of intrabony periodontal defects with synthetic materials such as Cerasorb has been shown to enhance periodontal regeneration. The aim of this study was to compare the effect of Cerasorb with autogenous bone graft (A.B.G) as a gold standard in treatment of two to three wall periodontal defects."nMaterials and Methods: In this interventional or randomized clinical trial study, 24 two to three wall intrabony defects were selected in a double blind manner. Defects were randomly (with tossing a coin) divided into two groups (test and control). Defects in test group were treated with flap surgery and Cerasorb. In control group, defects were treated with flap surgery and autogenous bone graft. At baseline and 3-month, 6-month and one-year follow up evaluations; clinical and radiographic assessments were performed. Data were statistically analyzed using the paired t test, Wilcoxon and Mann-whiteny. The level of significance was set at P<0.05. "nResult: At the 3-month, 6-month and one-year visits, the parameters of probing pocket depth (PPD), probing attachment level (PAL), bone level (distance between CEJ and alveolar crest), and bone density were not significantly difference in test and control groups (P>0.05). However, in each group there was significant difference in 4 parameters before and after surgery (P<0.05)."nConclusion: Treatment with Cerasorb compared to A.B.G produced the same results of improvement in two to three-wall intrabony defects. So the use of Cerasorb can be suggested for treatment of intrabony periodontal defects.